An Investigation of Multifaceted Relationship of Strength Based Approach - Hossain, Mir Sohrab; Khatun, Mahfuja; Khan, Sanjida (IJRDO - Journal of Business Management, 2018)
Strength based development approach is a new concept and not yet investigated vastly in the organization. In this paper the researcher has tried to identity some relationship between SBA and other variables like productivity, performance appraisal, turnover, job satisfaction etc. This is a literature review based paper which will help us to gain the knowledge of profound influence of SBA on numerous apsects of organization’s development. Organizations need to use SBA to be more competitive in the market place and gain competitive advantage over its rivals.